Laccase cataylzed synthesis of quaternary malononitriles with an aryl substituent - Parisa Amani; Mansour Shahedi; Elaheh Rezaei; Zohreh Habibi (Tetrahedron Green Chem)
Synthesis of quaternary malononitriles with an aryl substituent is of great importance because these scaffolds serve as essential intermediates in the synthesis of bioactive compounds. This study presents an efficient method for the laccase-catalyzed arylation of 2-substituted malononitrile derivatives by oxidation of catechols using aerial oxygen as the oxidant, followed by the nucleophilic addition of 2-substituted malononitriles. The process achieves yields ranging from moderate to excellent (73–97 %), and also, it was associated with a slight decrease in efficiency in higher scales.